A PROTOTYPE OF PAPER CUTTING MACHINE - Tran Vu, Minh; Tran, Tung (Journal of Applied Engineering Science, 2025)
Paper is a necessary component of life. It is used in a variety of settings, including offices, schools, and homes, enabling people to use it for a variety of tasks, including taking notes and packing. Typically, paper will be produced in a variety of sizes to match according to intended use. In the modern paper industry, larger machines are utilized to cut large stacks of paper, cardboard, or similar material. Such machines operate in a manner comparable to a guillotine. Commercial versions are motorized and automated and encompass clamping mechanisms to prevent material from shifting during the cutting process. The article proposes a paper cutter model using basic machine principles such as Geneva mechanism and chain transmission. Paper cutting is done by handwheel and lever mechanism. The main purpose of this machine is to reduce paper cutting time. The paper proposed a prototype of a paper cutting machine based on motion mechanism. The main target of the product is those people who need to cut paper not only at a low cost but also effectively. The project focuses on fabricating a machine that provides a simple and inexpensive paper cutting machine. Experimental results show that the cutting time for paper is less than 4 seconds. Moreover, the design of the proposed machine is mainly a mechanical aspect, the complicated controls methods aren’t needed.
Keywords: paper, prototype, cutting machine